(3GdQSGdI GdaJMjI aj GdCYeGd GdLjHjIs - (3eMeO Hf eMeO Hf CMeO GdZRGd GdOeTbqj, HOQ GdOjf, GdTgjQ HSHW GdeGQOjfj , J (B912 (3g` s
(3ChdgG (B:s
(3HYO GdOjHGLI agPg QSGdI ai GdYed HGdQHY GdeLjH eTJedg Ydi ebOeg hYTQjf HGHkG hSejJgG HGdQSGdI GdaJMjI s
(3BNQgG (B:s
(3hEf JSGhi GdHGbi MUI GdaLQ JhSW hbJ GdaLQ s
(3Vef eLehY , JQJjHgG (B: (3ef U (B48 - (3U(B51s
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B1 - (3U (B52 s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3ejbGJ (B1082) s
Keywords: (3Gdadcs